The Importance of Public Relations in the Creation of Destination Brand: Sample of Nevsehir - Selin, Unal Cimcek (European Scientific Journal, ESJ, 2017)
Today, to be able to become a destination brand our cities give a great deal of importance to distinguish themselves with their local-cultural values, identities and images. Public relations have significant contribution to the identification of a location as the destination brand which is introduced publicly. To ensure the attraction of tourists, the recognition of cities and their featuring in news is supplied through popular media and public relations strategies. As a destination of touristic city NevÅŸehir with its unspoiled nature, historical and cultural attractions, attracts the attention of visitors. In this study, in the process of the creation of NevÅŸehir destination branding, the importance of public relations and their practices will be analyzed.